The diagnosis of COVID-19 through X-ray images via transfer learning and fine-tuned dense layer on pipeline - Amiir Haamzah, Mohamed Ismail; Mohd Azraai, Mohd Razman; Ismail, Mohd Khairuddin; Muhammad Amirul, Abdullah; Rabiu Muazu, Musa; Anwar P. P., Abdul Majeed (Penerbit UMP, 2021)
X-ray is used in medical treatment as a method to diagnose the human body internally from diseases. Nevertheless, the development in machine learning technologies for pattern recognition have allowed machine learning of diagnosing diseases from chest X-ray images. One such diseases that are able to be detected by using X-ray is the COVID-19 coronavirus. This research investigates the diagnosis of COVID-19 through X-ray images by using transfer learning and fine-tuning of the fully connected layer. Next, hyperparameters such as dropout, p, number of neurons, and activation functions are investigated on which combinations of these hyperparameters will yield the highest classification accuracy model. InceptionV3 which is one of the common neural network is used for feature extraction from chest X-ray images. Subsequently, the loss and accuracy graphs are used to find the pipeline which performs the best in classification task. The findings in this research will open new possibilities in screening method for COVID-19.